PTH-299 Significance of the lymph node count after neo-adjuvant treatment for rectal cancer. (22nd June 2015) - Khan, MAS; Hakeem, AR; Scott, N; Botterill, I
Abstract : Introduction: Lymph node metastases is a significant prognostic indicator for disease recurrence in colorectal cancer (CRC) patients. The aim of this study was to assess the impact of short course radiotherapy (SCRT) and long course chemo-radiotherapy (CRT) on the number of lymph nodes retrieved for rectal cancer surgery and its ultimate outcome on disease recurrence. Method: Data for patients who underwent surgery alone or received SCRT or CRT followed by surgery for resectable primary rectal cancer from January 2005 till December 2010 were analysed. The primary outcomes measured were the number of lymph nodes retrieved, their status and disease recurrence. Patients with metastatic disease and palliative resections were excluded. Results: There were 434 patients. Of these 166 had surgery alone, 104 had short course radiotherapy and 164 had long course chemo-radiotherapy followed by surgical resection. The patients who received neo-adjuvant treatment were relatively younger. CRT decreased the retrieval of more than 12 lymph nodes, the median number of lymph nodes and the median number of metastatic lymph nodes as tabulated below (P < 0.001). Stage III was less common in CRT group (26%) than surgery alone (32%) and SCRT group (44%). Despite this 33.5% patients in CRT group had local and systemic disease recurrence as compared to 16% in surgery alone and 24% in SCRT group. This was statistically significant in CRT vs. surgery alone group (P < 0.001). Number of lymph nodes retrieved did not prove to be a significant prognostic indicator for disease free survival after CRT. Conclusion: Low lymph node count after CRT for rectal cancer surgery reflects the sensitivity to neo-adjuvant treatment and does not signify inadequate resection. This is the lymph node metastases and not the number of lymph nodes retrieved that is the prognostic factor for disease free survival. Disclosure of interest: None Declared.